Exploring the Role of Football Sponsorship in Brand Image formation : A Comparative Analysis of Betting, Financial Services, and Automotive Sponsors in the Czech Republic - Shapel, Alexey (2025)
This qualitative thesis investigates how audience perceptions, emotional connection, and brand image formation are shaped by sponsorship in Czech football. Thematic coding of the data and semi-structured interviews with Czech football fans of different involvement levels served as the foundation for this qualitative study. The research focused on three specific sponsor industries present in Czech football: financial services, automotive, and gambling. The findings indicated that fan perceptions significantly differed across industries and were influenced by sponsor visibility, cultural fit within the Czech context, and brand reliability. Gambling sponsors were mainly seen to be overpromoted and irritating, with a high risk of social harm. The automotive industry was characterised by a strong cultural fit among Czech football fans, fostering national pride through the domestic brand Škoda. Traditional banks were seen as more acceptable and trustworthy than the modern financial platforms, which were emphasised as highly complex and risky, limiting the positive emotional perceptions among the Czech audience.